lac Repressor blocks transcribing RNA polymerase and terminates transcription. - Deuschle, U (1986)
Operator sequences are essential elements in many negatively controlled operons. By binding repressors, they prevent the formation of active complexes between RNA polymerase and promoters. Here we show that the Escherichia coli lac operator-repressor complex also efficiently interrupts ongoing transcription. This observation suggests a mechanism of action for operators located distal to promoter sequences.